PENDIDIKAN ISLAM DALAM KAJIAN HISTORY - Yahdi, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2022)
Islamic education has its own characteristics, especially in history, has become a historical reality that can be taken in various forms in the development of Islamic education and education in general. Throughout the history of Islamic education, it has always appeared with its own characteristics despite the various dynamics of education, society and human culture. Its distinctive feature is the development of intellectual capacity and heart strengthening, intellectual and spiritual development. This paper contains various things that show the special values ​​of Islamic education such as the nature of education, terms of Islamic education, objects of Islamic education, and the historical methodology of Islamic education. The specificity of Islamic education can be seen from the terms used such as tarbiyah, ta'lim and ta'dib. Tarbiyah leads to the strengthening of faith as the basis of human knowledge. Ta'lim leads to intellectual development while ta'dib leads to self-formation and individual personality.